Cinema and Polish-Ukrainian Relations Between the 1990s and 2010s - Krupnyk, Liubov (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article reviews the role of feature films that recreate the conflictual relations of the shared history which Poland and Ukraine look at from significantly different vantage points. It analyzes these films’ influence on Polish-Ukrainian relations, as well as the results of the Polish-Ukrainian dialogue. Using examples of Polish films that were commercially successful – With Fire and Sword by Jerzy Hoffman (1999) and Volyn by Wojciech Smarzowski (2016) – the article traces how cinema can articulate the problems of shared history that exist in the collective memory, and what kind of results it brings.